Factors Associated with Adolescent Girls' Knowledge of Fluor Albus at Taman Harapan 1 SHS, Bekasi City, in 2016 - Pansilia, Pansilia; Muslimah, Rifa’at Hanifa (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Fluor albus (vaginal discharge) affects approximately 50% of the female population across almost all age groups. In Indonesia, over 75% of women experience fluor albus at least once in their lifetime. This high prevalence is associated with the country’s humid climate, which facilitates the growth of pathogenic fungi and bacteria. Objective: To identify the factors associated with adolescent girls’ knowledge regarding fluor albus. Method: This study employed a descriptive-analytic design with a cross-sectional approach. Results and Discussion: Of the respondents, 122 adolescent girls (61.0%) demonstrated low knowledge of fluor albus, while 78 (39.0%) showed a high level of knowledge. Bivariate analysis revealed that personal hygiene (p = 0.003), sources of information (p = 0.005), and environmental factors (p = 0.001) were significantly associated with knowledge levels regarding fluor albus. These three variables were identified as significant factors influencing adolescent girls' knowledge. The findings suggest that improving adolescent knowledge requires: (1) enhancement of personal hygiene practices, (2) increased access to accurate and reliable information through various media, and (3) supportive family and social environments. Conclusion: Health education interventions targeting adolescents should adopt a holistic approach, encompassing improvements in personal hygiene, facilitation of access to health information, and the creation of supportive environments.